MULLA SHADRA [1571 M - 1636 M] (STUDY TENTANG PEMIKIRAN AL-HIKMAH AL-MUTA’ALIYAH DAN AL-ASFAR AL-ARBA’AH) - Muhammad Aziz (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
After Ibn Rushd, the Muslim world has almost certainly lost a strong leader in the field of science. All this is correct if seen from the perspective of Sunnis. But it is not for the Shia for having a prominent figure like Mulla Sadra that is considered to have brought fresh air to the world of philosophy (especially al-hikmah al-muta'aliyah). This paper will discuss about who Mulla Sadra is and the characteristics of thinking about al-hikmah al-muta'aliyah and al-asfar al-arba'ah. By using historical analysis, the writer finds that the Mulla Sadra's transcendental theosophy or al-hikmah al-muta'aliyah is a kind of wisdom teachings based on three principles, namely intellectual intuition (dzawq or ishraq), rational ('aql or istidlal), and shari'ah. In addition, the fundamental principle underlying it is the concept of ashalat al-wujud, tasykik al-wujud and wahdat al-wujud. One of the teachings is about four human journeys to obtain the truth of God correctly. The four journeys are ; 1). The journey from the created world (al-Khalq), the visible world, leading to the world of the creator, the world the real truth (al-Haqq), 2). The journey in a true righteousness (al-Haqq) through the true knowledge (al-Haqq), 3). The journey from the the Most True toward the created world, through the true knowledge obtained from the two stages above, and 4). The journey along with the Most True in the created world.